Isolasi Kitosan Dari Tudung Jamur Merang (Vollvariella Volvaceae) Dan Aplikasinya Sebagai Absorben Logam Timbal (Pb) - Tanasale, Matheis F.J.D.P.; Bandjar, Adriani; Sewit, Natasya (Indonesian Journal of Chemical Research, 2018)
Chitosan isolated from mushroom (Vollariella volvaceae) as adsorbent of lead (Pb) metal has been done. The isolation of chitosan was obtained 2.94% from total weight of mushroom. Fungtional groups of chitin and chitosan were indentified by using FTIR spectrophotometry. The chitosan had 74.66% degree of deacetylation and 2.09 x 104 g/mol viscosity molecular weight. The experimental data of the chitosan as adsorbent for Pb metal were correlated with the Langmuir and Freundlich isotherm model. The maximum adsorption capacity of Pb based on the Langmuir isotherm model was 2.66 mg/g.